Workshop on low-temperature scanning electron microscope : proceedings - Tropical Architecture Workshop (1993 : Australia); Australian Institute of Tropical Architecture (Australia : Australian Institute of Tropical Architecture, 1993)
The Traditional Malay Architecture - An Intelligent Building / Md Rajeh Salleh